Combined direct-sun ultraviolet and infrared spectroscopies at Popocatépetl volcano (Mexico) - N. Taquet; C. Rivera Cárdenas; W. Stremme; T. Boulesteix; A. Bezanilla; M. Grutter; O. García; F. Hase; T. Blumenstock (Frontiers in Earth Science, 2023)
Volcanic plume composition is strongly influenced by both changes in magmatic systems and plume-atmosphere interactions. Understanding the degassing mechanisms controlling the type of volcanic activity implies deciphering the contributions of magmatic gases reaching the surface and their posterior chemical transformations in contact with the atmosphere. Remote sensing techniques based on direct solar absorption spectroscopy provide valuable information about most of the emitted magmatic gases but also on gas species formed and converted within the plumes. In this study, we explore the procedures, performances and benefits of combining two direct solar absorption techniques, high resolution Fourier Transform Infrared Spectroscopy (FTIR) and Ultraviolet Differential Optical Absorption Spectroscopy (UV-DOAS), to observe the composition changes in the Popocatépetl’s plume with high temporal resolution. The SO2 vertical columns obtained from three instruments (DOAS, high resolution FTIR and Pandora) were found similar (median difference <12%) after their intercalibration. We combined them to determine with high temporal resolution the different hydrogen halide and halogen species to sulfur ratios (HF/SO2, BrO/SO2, HCl/SO2, SiF4/SO2, detection limit of HBr/SO2) and HCl/BrO in the Popocatépetl’s plume over a 2.5-years period (2017 to mid-2019). BrO/SO2, BrO/HCl, and HCl/SO2 ratios were found in the range of (0.63 ± 0.06 to 1.14 ± 0.20) × 10−4, (2.6 ± 0.5 to 6.9 ± 2.6) × 10−4, and 0.08 ± 0.01 to 0.21 ± 0.01 respectively, while the SiF4/SO2 and HF/SO2 ratios were found fairly constant at (1.56 ± 0.25) × 10−3 and 0.049 ± 0.001. We especially focused on the full growth/destruction cycle of the most voluminous lava dome of the period that took place between February and April 2019. A decrease of the HCl/SO2 ratio was observed with the decrease of the extrusive activity. Furthermore, the short-term variability of BrO/SO2 is measured for the first time at Popocatépetl volcano together with HCl/SO2, revealing different behaviors with respect to the volcanic activity. More generally, providing such temporally resolved and near-real-time time series of both primary and secondary volcanic gaseous species is critical for the management of volcanic emergencies, as well as for the understanding of the volcanic degassing processes and their impact on the atmospheric chemistry.